PEMANFAATAN LIMBAH FLY ASH DAN BOTTOM ASH DARI PLTU SUMSEL-5 SEBAGAI BAHAN UTAMA PEMBUATAN PAVING BLOCK - Hadi Winarno; Damris Muhammad; Yudha Gusti Wibowo (Universitas Islam Lamongan, 2019)
Fly ash and bottom ash are solid waste from coal combustion in the operating system of Steam Power Plant (PLTU). The research was conducted by combining fly ash and bottom ash with an adhesive consisting of portland cement. Based on the tests performed the maximum mixture obtained with cement samples, fly ash and bottom ash is 1: 2: 2. Paving blocks made from fly ash and bottom ash have compressive strength values resulting in compressive strength values of 50.52 MPa. This value indicates that the sample is in the class of paving blocks A. Paving Block made from fly ash and bottom ash also has a very good average air absorption value, in a combination of suitable cement mixtures, fly ash and bottom ash (1: 2: 2) the average air absorption value is still 5.06%. This value shows that the sample is in class B paving blocks.